Ley Orgánica de las Zonas de Empleo y Desarrollo Económico (ZEDE) - La Editora (La Revista de Derecho, 2015)
DOI: http://dx.doi.org/10.5377/lrd.v34i0.1768 Revista de Derecho, Vol. 34, Nº 1, Año 2013: 113-129